2019
DOI: 10.1186/s41935-019-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Height estimation from head dimensions in South-South Nigeria

Abstract: Background: Height estimation is an important stage of forensic investigation to identify an unknown person. The problem of unidentified human remains in the study area, due to local militia activities, kidnapping, and murder, necessitated this study to assess the correlation between the body height and head dimensions and to formulate regression models for estimation of height that are population and gender-specific. Materials and methods: The study involved 952 subjects (464 males and 488 females), aged 18-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(24 reference statements)
2
4
1
Order By: Relevance
“…Studies by Patil et al [6], Hamed et al [19], Selarka et al [20], and Eboh et al [21] reported slightly higher mean ages compared to the present study. Cossellu et al [22], Soman et al [23], and Shireen et al [1] had a lower age limit lower than the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies by Patil et al [6], Hamed et al [19], Selarka et al [20], and Eboh et al [21] reported slightly higher mean ages compared to the present study. Cossellu et al [22], Soman et al [23], and Shireen et al [1] had a lower age limit lower than the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…9 Eboh et al carried out a study on the Nigerian population and reported that the left frontal sinus width and height were statistically significant. 14 In the present study also, the left frontal sinus height was statistically significantly difference (p < 0.05) between males and females, while there was no significant difference in the other variables (p > 0.05).…”
Section: Discussionsupporting
confidence: 54%
“…8 Similarly, Eboh et al 14 performed a study based on sex determination of frontal sinus on which a cutoff value of 0.5 was established, which meant that when it was !0.5, the individuals were classified as males and if it was less than 0.5 it was female. 14 According to the present study, an ROC curve analysis was used and the area under the curve of our model was 0.733. The optimum cutoff value for predicted probability was 0.489 (►Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that sex determination using FS diameters was successful for 68.2% of the males and 71.2% of the females, while the accuracy rate for both sexes was 69.7%. The literature contains studies using different imaging techniques for sex determination based on FS [21][22][23][24][25][26][27][28]. In a study conducted in India with computed tomography (CT), it was reported that sex determination had an accuracy rate of 61.4% [21], and in a direct radiography study, the accuracy of sex determination was determined as 59% [22].…”
Section: Discussionmentioning
confidence: 99%